Paid Consulting in Ontario Colleges of Applied Arts and Technology - Bell, Stephen; Jones, Glen A. (Canadian Journal of Higher Education, 1992)
A survey of faculty participation in paid consulting arrangements in Ontario Colleges of Applied Arts and Technology reveals that 34% were involved in at least one project during a specified one-year period. There was significant variation in participation by division of academic appointment and by gender. The authors suggest that further research should be undertaken concerning the nature and role of paid consulting in community colleges. A number of basic questions are raised in an attempt to induce further study on this important topic.